2021
DOI: 10.1080/07388551.2021.1965952
|View full text |Cite
|
Sign up to set email alerts
|

Membrane bioreactors for syngas permeation and fermentation

Abstract: Syngas fermentation to biofuels and chemicals is an emerging technology in the biobased economy. Mass transfer is usually limiting the syngas fermentation rate, due to the low aqueous solubilities of the gaseous substrates. Membrane bioreactors, as efficient gas-liquid contactors, are a promising configuration for overcoming this gas-to-liquid mass transfer limitation, so that sufficient productivity can be achieved. We summarize the published performances of these reactors. Moreover, we highlight numerous par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…Increasing the surface area of the membrane per unit working volume AS/VL to 62.5 m −1 , and reducing the pressure to 37.23 kPa, achieved a higher volumetric mass transfer coefficient k La of 155.16 h −1 . 87 Elisiario et al 88 reported that silicone membranes are highly resistant to mechanical and chemical stress, unlike microporous membranes, and they are not susceptible to pore clogging, biofouling or liquid entry in the pores. 88 The simplicity of operation and control has made CSTR the most used reactor in research laboratories and industrial settings.…”
Section: Gas-liquid Mass Transfermentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing the surface area of the membrane per unit working volume AS/VL to 62.5 m −1 , and reducing the pressure to 37.23 kPa, achieved a higher volumetric mass transfer coefficient k La of 155.16 h −1 . 87 Elisiario et al 88 reported that silicone membranes are highly resistant to mechanical and chemical stress, unlike microporous membranes, and they are not susceptible to pore clogging, biofouling or liquid entry in the pores. 88 The simplicity of operation and control has made CSTR the most used reactor in research laboratories and industrial settings.…”
Section: Gas-liquid Mass Transfermentioning
confidence: 99%
“…87 Elisiario et al 88 reported that silicone membranes are highly resistant to mechanical and chemical stress, unlike microporous membranes, and they are not susceptible to pore clogging, biofouling or liquid entry in the pores. 88 The simplicity of operation and control has made CSTR the most used reactor in research laboratories and industrial settings. 89 Table 3 provides a summary of some widely used bioreactors, presenting how they perform during syngas fermentation.…”
Section: Gas-liquid Mass Transfermentioning
confidence: 99%
“…Trickle bed reactors have a thin liquid film contacting the gas phase and, therefore, a low liquid resistance to mass transfer [133]. Membrane reactors could reach a maximum k L a of 1096 h -1 at laboratory scale, which is three times higher than that of industrially used bubble columns [134]. However, due to the high membrane costs, they are less suitable for the production of bulk chemicals like ethanol [134].…”
Section: Hardwarementioning
confidence: 99%
“…Membrane reactors could reach a maximum k L a of 1096 h -1 at laboratory scale, which is three times higher than that of industrially used bubble columns [134]. However, due to the high membrane costs, they are less suitable for the production of bulk chemicals like ethanol [134]. Another possibility to achieve high mass transfer rates but with low operational and maintenance costs are bubble and gas-lift reactors.…”
Section: Hardwarementioning
confidence: 99%
“…Experimental and computational system‐level analyses of a growing number of gas‐fermenting processes supported a better understanding of cellular behaviour and of its application in biocatalytic systems' development (de Lima et al, 2022 ; Ghadermazi et al, 2022 ; Mahamkali et al, 2020 ; Molitor et al, 2017 ; Valgepea et al, 2017 ). Additionally, several studies focused on the development of efficient reactor configurations combining enhanced gas‐to‐liquid mass transfer with low power consumption (Asimakopoulos et al, 2018 ; Elisiario et al, 2022 ; Stoll et al, 2019 ; Takors et al, 2018 ). Over the past several years, synthetic biology approaches have been employed to develop acetogens in efficient platform strains for C 1 gas conversion, focusing in particular on the manipulation of metabolic fluxes aimed at the production of non‐native compounds (Bourgade et al, 2021 ; Lee et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%